Proposing a Model of Technology Acceptance and use in Digital Banking: A Systematic Review and Meta-Analysis Approach - Suwito, Justin Hadinata; Panjaitan, Erwin Setiawan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The advancement of information technology has driven a significant transformation in the banking sector through digital banking, which has now become the backbone of modern financial services. Digital banking offers efficiency, ease of transactions, and reduced operational costs. Despite these benefits, challenges remain, particularly the high initial investment costs and the complexity of customer adoption. Without a well-designed user acceptance strategy, substantial investments risk being underutilized. Therefore, a deep understanding of the factors influencing digital banking adoption is crucial to ensure the effectiveness of digital transformation initiatives. Previous studies have examined the acceptance and use of digital banking using popular models such as TAM, UTAUT, and UTAUT2. However, fragmented findings—caused by variations in results and the inclusion of additional variables—pose challenges for generalization. This study aims to develop a more comprehensive model of digital banking acceptance through a systematic review and meta-analysis. The results indicate that most core constructs of UTAUT2—such as Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, Habit, Price Value, and Hedonic Motivation—are significant. Furthermore, external variables such as Trust, Perceived Security, Enterprise Image, Promotions, and Perceived Risk also play a role, thereby extending the model beyond the generic framework. The proposed model is expected to enrich the development of technology acceptance theory by introducing a context-specific framework for digital banking. It also provides strategic guidance for the banking industry to enhance adoption through targeted interventions on the most influential variables. Consequently, this model can serve as a stronger foundation for both institutional practices and future research in the field.